Compensation and the Abandoned Property of the 1948 Palestinian Refugees: Assessment and Implications - Frank D Lewisf (Queen's University, Department of Economics, 2006)
This paper extends the analysis of "Agricultural Property and the 1948 Palestinian Refugees: Assessing the Loss" (Lewis 1996) to non-agricultural property. The estimate is based mainly on the area of urban property abandoned by refugees, where valuations are based on contemporary transfer prices, tax payable on the property, and inferences about rent. The amounts are much higher than those derived by the United Nations Conciliation Commission in 1951. Still the total implied by this paper and (Lewis 1996) is such that if Israel were to pay the overall loss as compensation, the transfers are unlikely to have a serious impact on their economy
Keywords: 330; Palestine; Flüchtlinge; Enteignung; Verlust; Reparationen; Israel; Palästina